Development of Anecdotal Text Writing Module Assisted by Stand-Up Comedy for Grade X Students of Madrasah Aliyah - Seppi Yeni; Elmustian Elmustian; Mangatur Sinaga (FKIP - Universitas Riau, 2026)
This study aims to develop a Stand-Up Comedy–based module for teaching anecdotal writing to 10th-grade Madrasah Aliyah students. Writing anecdotal texts requires critical and creative thinking skills; therefore, engaging, contextual, and relevant learning media are needed. This research employed a Research and Development (R&D) design using the ADDIE model through quantitative and qualitative approaches. Quantitative data were obtained from pretests and posttests in control and experimental classes, while qualitative data were collected through interviews with students and teachers. The needs analysis revealed that students struggled to understand the structure and humor elements of anecdotal texts, yet showed high interest in stand-up comedy. Expert validation of the material, language, cultural, and media aspects indicated a feasibility level of 95.83%–100%, meaning the module was highly feasible with minor revisions. Implementation of the module resulted in a significant improvement in students’ writing skills. At MA Darul Hikmah Pekanbaru, the average score increased from 63.5 to 75.8, while at MA Ummatan Wasathan, it increased from 60 to 73.5. The Stand-Up Comedy–based module effectively enhanced students’ understanding of structure, creativity, and their ability to express criticism humorously. Overall, this research offers an instructional innovation by integrating popular comedy media into Indonesian language learning, producing a valid, practical, and effective module.